2018
DOI: 10.1101/323584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the human volume regulated anion channel

Abstract: SWELL1 (LRRC8A) is the only essential subunit of the Volume Regulated Anion Channel (VRAC), which regulates cellular volume homeostasis and is activated by hypotonic solutions. SWELL1, together with four other LRRC8 family members, forms a vastly 20 heterogeneous cohort of VRAC channels with different properties; however, SWELL1 alone is also functional. Here, we report a high-resolution cryo-electron microscopy structure of full-length human homo-hexameric SWELL1. The structure reveals a trimer of dimers asse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 41 publications
6
40
1
Order By: Relevance
“…VRAC operates as a heteromeric complex of several proteins from the LRRC8 family. Since the molecular structure of VRAC was identified, a series of antibodies against different regions of the basic subunits of the family LRRC8 have been developed and effectively used [4,5,9,14,17,18,[23][24][25][26]. Before now, VRAC subunit proteins were detected mostly by immunoblotting of the solubilized whole cells [27][28][29][30][31][32], less often of cell membranes lysates [14,33,34] or by imaging cells that have been permeabilized for staining [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VRAC operates as a heteromeric complex of several proteins from the LRRC8 family. Since the molecular structure of VRAC was identified, a series of antibodies against different regions of the basic subunits of the family LRRC8 have been developed and effectively used [4,5,9,14,17,18,[23][24][25][26]. Before now, VRAC subunit proteins were detected mostly by immunoblotting of the solubilized whole cells [27][28][29][30][31][32], less often of cell membranes lysates [14,33,34] or by imaging cells that have been permeabilized for staining [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicate that VRAC and their obligatory subunit, LRRC8A have critical roles in many cell functions including cell motility, proliferation, apoptosis, drug and metabolite transport, angiogenesis, and spermatid development, as well as in cell pathophysiological cell functions such as cancer drug resistance, ischemic brain edema, and glaucoma [7][8][9][10][11][12][13][14][15][16][17]. While the molecular structure of VRAC is well documented [18], understanding how VRAC expression at the membrane is regulated has been poorly explored due to lack of appropriate methodology. Electrophysiological methods are suitable for investigating biophysical properties of channels in a single cell and during short-time events but are unsuitable for studying cell populations and the long-term alteration of cells.…”
Section: Introductionmentioning
confidence: 99%
“…The LRRC8 protein family embraces the five members LRRC8A/B/C/D/E, which are all membrane-spanning proteins composed of four trans-membrane domains and a long C-terminal leucine-rich repeat domain (LRRD) [40,41]. As sequence analyses indicated that the LRRC8 family are related to pannexins’ channel complexes, which release larger signaling molecules as ATP from the cytoplasm to the extracellular environment [42,43], it has been suggested that LRRC8 proteins may form multimeric channel complexes with varying LRRC8 protein stoichiometry [41,42].…”
Section: Cellular Cisplatin Accumulationmentioning
confidence: 99%
“…As sequence analyses indicated that the LRRC8 family are related to pannexins’ channel complexes, which release larger signaling molecules as ATP from the cytoplasm to the extracellular environment [42,43], it has been suggested that LRRC8 proteins may form multimeric channel complexes with varying LRRC8 protein stoichiometry [41,42]. Protein sequence analysis has revealed that LRRC8A contains putative cisplatin-interacting methionines in the cellular and transmembrane segments as well as CxxC/YxxY motifs that can be oxidized/phosphorylated, but their significance for the facilitation of cisplatin uptake has yet to be revealed.…”
Section: Cellular Cisplatin Accumulationmentioning
confidence: 99%
See 1 more Smart Citation